Effects of glucokinase haploinsufficiency on the pancreatic β‐cell mass and function of long‐term high‐fat, high‐sucrose diet‐fed mice - Ikumi Shigesawa; Akinobu Nakamura; Yuki Yamauchi; Shinichiro Kawata; Asuka Miyazaki; Hiroshi Nomoto; Hiraku Kameda; Yasuo Terauchi; Tatsuya Atsumi (Journal of Diabetes Investigation)
ABSTRACT Aims/Introduction We previously showed that glucokinase haploinsufficiency improves the glucose tolerance of db/db mice by preserving pancreatic β‐cell mass and function. In the present study, we aimed to determine the effects of glucokinase haploinsufficiency on the β‐cell mass and function of long‐term high‐fat, high‐sucrose (HFHS) diet‐fed mice. Materials and Methods Four‐week‐old male glucokinase haploinsufficient (Gck+/−) mice and 4‐week‐old male wild‐type (Gck+/+) mice (controls) were each divided into two groups: an HFHS diet‐fed group and a normal chow‐fed group, and the four groups were followed until 16, 40 or 60 weeks‐of‐age. Their glucose tolerance, glucose‐stimulated insulin secretion and β‐cell mass were evaluated. In addition, islets were isolated from 40‐week‐old mice, and the expression of key genes was compared. Results Gck+/−HFHS mice had smaller compensatory increases in β‐cell mass and glucose‐stimulated insulin secretion than Gck+/+HFHS mice, and their glucose tolerance deteriorated from 16 to 40 weeks‐of‐age. However, their β‐cell mass and glucose‐stimulated insulin secretion did not decrease between 40 and 60 weeks‐of‐age, but rather, tended to increase, and there was no progressive deterioration in glucose tolerance. The expression of Aldh1a3 in pancreatic islets, which is high in several models of diabetes and is associated with an impairment in β‐cell function, was high in Gck+/+HFHS mice, but not in Gck+/−HFHS mice. Conclusions Glucokinase haploinsufficiency prevents the progressive deterioration of pancreatic β‐cell mass/function and glucose tolerance in long‐term HFHS diet‐fed mice.